Moving Least Squares Method for a One-Dimensional Parabolic Inverse Problem - Baiyu Wang (Abstract and Applied Analysis)
This paper investigates the numerical solution of a class of one-dimensional inverse parabolic problems using the moving least squares approximation; the inverse problem is the determination of an unknown source term depending on time. The collocation method is used for solving the equation; some numerical experiments are presented and discussed to illustrate the stability and high efficiency of the method.